Early Hepatotoxicity of Methotrexate in Rheumatoid Arthritis (TAJ: Journal of Teachers Association, 2009)
The present study was undertaken to evaluate methotrexate induced early hepatotoxicity in rheumatoid arthritis patients. This study was carried out on ARA criteria fulfilling 35 diagnosed rheumatoid arthritis patients of either gender, aged 20-60 years, presented in Medicine Department of Rajshahi Medical College Hospital, Rajshahi from July 2007 to June 2008. Patients with normal liver function tests and HBsAg and anti-HCV negative cases were given oral Methotrexate (10-25mg/week) for 3 months. Baseline level of SGPT, serum bilirubin and prothrombin time was 10.07±0.32u/l, 0.59±0.03mg/dl and 12.97±0.34 seconds respectively. After 3 months of methotrexate therapy, level of SGPT, serum bilirubin and prothrombin time was found to be 12.60±1.16 u/l, 0.70±0.06mg/dl and 13.87±0.45 seconds respectively. During methotrexate therapy SGPT level changed significantly (p